Combination of soil solarization, vesicular-arbuscular mycorrhiza and Azotobacter chrococcum for the management of seedling wilt of citrus - and S.D. SHARMA, HARENDER RAJ* (Indian Phytopathology, 2010)
A study was conducted during 2002 to 2004 at Nauni and Bhota to find out the effect of root inoculation of seedlings of citrus (Citrus jambiri Lush.) with native isolates of vesicular-arbuscular mycorrhiza and Azotobacter chrococcum on the incidence of seedling wilt caused by Fusarium solani and Rhizoctonia solani and also on shoot and root growth of the seedlings. These treatments were evaluated in soil which was solarized with transparent polyethylene mulch for 40 days in May-June, soil sterilized with 5 % formaline and also in untreated soil. In general, inoculation of citrus seedlings with native isolates of va-mycorrhiza and A.chrococcum resulted in decrease in the incidence of seedling wilt and increase in shoot and root length in treated and untreated soil. However, inoculation of seedlings with AMUHF4 (Gigaspora sp.) isolates of vamycorrhizaand AZUHF1 isolate of A.chrococcum and their planting in solarized soil was found most effective with no incidenceof seedling wilt in comparison to 33.6 % in control accompanied with 71.1 % increase in shoot length and 74.3 % increase inroot length.